Kapitalismus und Naturzerstörung Zur kritischen Theorie des gesellschaftlichen Naturverhältnisses - Stache, Christian (Verlag Barbara Budrich, 2017)
Historical-materialistic critique of common explanations of the social relationship to nature in capitalism brings to light idealistic, culturalistic and politicistic short-cuts. A critical theory of social nature relations based on Marx's major work Das Kapital shows that the laws of capitalist society necessarily lead to systematic destruction of nature. The capitalist mode of production is incompatible with sustainable development.